An X3D Framework for Developing Adaptive Virtual Environments - Lopes, Luiz Fernando Braga; Dias Junior, José Barbosa; Damasceno, Eduardo Filgueiras; Cardoso, Alexandre; Lamounier Junior, Edgard Afonso (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2010)
This work describes the concepts related to Adaptive Interfaces and presents a framework model for the management of Interaction Interfaces in Virtual Reality Environments. To that aim, characteristics of Adaptive Virtual Environments, as well as the technologies needed for the development of Virtual Reality Interfaces were identified. In addition to that, an Artificial Intelligence model was adopted for the reorganization of information based on user interaction in a specific digital teaching context. The combination of these three elements forms the basis of this adaptive framework, which provides an environment favorable to the development of specific educational approaches trough the generation of individualized contexts.